Draft Annual Plan 1999-200 A Supplement of Volume II - Planning Commission (Planning Commission, 1999)
Statement III Schemewise Outlays and Expenditure. Major Head Of Development:101-Agriculture and Allied Activities Minor Head of Development:101.2401-Crop Husbandry
Government of Uttar Pradesh State Planning Commission